Hack/slash: resurrection (2017), volume 1 ebook Resurrection vol. 1. - Howard, Tini (Hack/Slash: Resurrection (2017), 2018)
The fan-favorite title returns with hot new writer, TINI HOWARD! Cassie Hack has been living off the grid, but when a new monstrous threat arises to torment the kids at Camp Indigo River, it's time for Cassie to pick up the baseball bat once again! Gory, sexy, twisted, and funny...HACK IS BACK! Collects HACK/SLASH RESURRECTION #1-6. Author: Tini Howard. Illustrator: Celor, K. Michael Russell . 2018 Hack/Slash, Inc..